EXPLORING THE STRUCTURE AND EVOLUTION OF THE NOVOSIBIRSK BIOMEDICAL CO-AUTHORSHIP NETWORK - I. I. Titov; A. A. Blinov (Вавиловский журнал генетики и селекции)
The interaction diversity within the communities of living matter, from bacterial colonies to human societies, makes them inherently more complex than ensembles of particles in inanimate nature. Co-authorship networks are a particular case of intra- and inter-group social interactions. In this paper, we analyze the Novosibirsk biomedical scientific community as an example of such a network. Using the PubMed database, we have built a community network and calculated its statistics. The distribution of organizations by scientific activity has a fat tail and obeys the Pareto principle: 83% of publications and 75% of authors belong to the 20% of the most active organizations. A comparison of their networks shows that networks of the universities have a more pronounced core rather than those of research institutions. We have plotted the “demographic” structure of currently active authors and found out two facts: (1) an abundance of authors with short “publication experience” and (2) a deficit of authors whose first publication is dated back to 1991-1997. In general, the network dynamics is non-steady, and the activity tends to increase.